Comparison of VATS and limited axillary thoracotomy in the treatment of spontaneous pneumothorax: a cross-sectional study - Hasan Oguz Kapicibasi (Journal of the Pakistan Medical Association, 2021)
Objective: To compare the results of conventional mini axillary thoracotomy with video-assisted thoracic surgery in the treatment of spontaneous pneumothorax. Method: The retrospective study was conducted at at Izmit Seka State Hospital, Kocaeli, Turkey, and Çanakkale Onsekiz Mart University Teaching Hospital, Çanakkale, Turkey, and comprised data from November 2011 to May ??2019 of patients who underwent surgery for spontaneous pneumothorax either with video-assisted thoracic surgery, who were placed in Group A, ?or axillary thoracotomy, who wewre placed in Group B. Data gathered related to age, gender, operation side, smoking status, postoperative hospital stay, recurrence rates, and postoperative complications. Data was analysed using SPSS 25. Results: Of the 75 patients, 60(80%) were male and 15(20%) were female. The overall mean age was 29.37±11.60 years. Group A had 41(54.7%)patients, while Group B had 34(45.3%). Postoperative recurrence was not encountered in any patient in Group B, while 2(5.4%) patients in Group A had a recurrence (p>0.05) who both continued smoking. Hospital stay was significantly higher in Group B (p?<0.001).? Conclusion: Video-assisted thoracic surgery in the treatment of spontaneous pneumothorax was found to shorten hospital stay, and can be used more widely. Continuous...